Modified wet rendering oil extraction from milkfish (Chanos chanos) fish waste for potential biodiesel feedstock. - Acepcion, Ace Amalechiar Daradar (2023.)
Chanos chanos fish wastes are the discarded parts including the internal organs, viscera, bones, trimmings, tails, fins, and skin. Particularly, viscera is discarded during the bangus deboning process. These discarded portions while disposing cause major environmental damage. Usually, the discarded parts of fishes are ground into fishmeal for livestock and aquaculture feed. This study was undertaken to optimize the wet rendering oil extraction of Chanos chanos waste by using Box-Behnken design. It further investigated on the potentiality of the extracted oil as biodiesel feedstock. Waste samples were collected from Roxas City and Miag-ao market. The samples were homogenized and then heated at varying heating time, heating temp, and amount of water. Optimal parameters were determined to be 37.55 min, 70°C, and 0.79:1 (v/w) water to sample ratio (v/w) with a yield of 88.89±1.02%. Physicochemical characteristics were carried out and the results suggest that Moisture Content = 0.30%, Ash Content=0.123%, and Specific Gravity=0.9012, of oil extracted was within the standards of biodiesel. However, Acid Value= 15.86 mgKOH/g and Peroxide Value = 349.61 mEq/kg indicate that it is essential to add an additional pre-treatment step to reduce acid value of oil in preparation for biodiesel production.
Thesis (Undergraduate, Bachelor of Science in Chemical Engineering) School of Technology, University of the Philippines Visayas, Miagao, Iloilo. 2023.
Keywords: Milkfish fish wastes